The case of the cheese thief - Bright, J. E; Neely, Scott (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2014)
On a trip through Europe, Scooby-Doo and the gang encounter the mystery of the missing million-dollar mozzarella--and they need the reader's help to solve the mystery and find the cheese
"12 possible endings"--Cover
English stories
GRL: S
007-012
1 2 13
NEW_ZTN_GN
Keywords: Scooby-Doo -- (Fictitious character) -- Juvenile fiction; Detective and mystery stories; Great Dane -- Juvenile fiction; Mozzarella cheese -- Juvenile fiction; Plot-your-own stories; Cheese -- Fiction; Dogs -- Fiction; Mozzarella cheese -- Fiction; Mystery and detective stories; Plot-your-own stories; Mystery fiction